Columbus and the world around him - Meltzer, Milton, 1915-2009. (New York : Franklin Watts, 1990)
Describes the voyages of Columbus, the terrible impact of the Spaniards on the Indians, and the ultimate cultural influence of the Native Americans on their white conquerors.
Only Three Continents -- To Serve God and Grow Rich -- A New Age Begins -- Going to Sea -- The Street Corner of Europe -- The Great Enterprise of the Indies -- Three Ships and Ninety Men -- Land! Land! -- The People of the New World -- "I Could Overrun All These Islands ..." -- Admiral of the Ocean Sea -- The Second Voyage -- Gold Hunts and Manhunts -- Columbus in Chains -- The Last Voyage -- Changing the World.
Includes bibliographical references (pages 183-185) and index.
Keywords: Columbus, Christopher -- Juvenile literature; Columbus, Christopher; Columbus, Christopher; Explorers -- Spain -- Biography -- Juvenile literature; Explorers -- America -- Biography -- Juvenile literature; America -- Discovery and exploration -- Spanish -- Juvenile literature; Explorers; America -- Discovery and exploration -- Spanish; Discovery and exploration, Spanish; Explorers; America; Spain; America -- Exploration -- Spanish -- Juvenile literature; America -- Exploration -- Spanish; Biographies; Juvenile works; Biographies; Biography